JURIDICAL ANALYSIS OF BORDER AREA LAND REGISTRATION AND CONSOLIDATION FROM AN ECOSYSTEM PERSPECTIVE THE ERA OF FIVE POINT ZERO DESTRUCTION - Ginting, Lilawati; Eddy, Triono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Land Registration and Consolidation is a policy in the agrarian and land sector which in a constitutionalist approach is an obligation of the Government in all dimensions of Government management and administration, public services, and all aspects and dimensions of the National life system. Therefore, the author is determined to present the central theme in this journal, namely with the title "Judicial Analysis of Border Area Land Registration and Consolidation in the Ecosystem Perspective of the Five Point Zero Disruption Era".  This type of journal writing focuses on the type of normative legal writing. The data used to analyze the problem in question relies on secondary data. The approach methodology is carried out using legal research, through library research, prioritizing qualitative analysis. The theory used to analyze the problem formulation framework in question is by applying Volkgeist theory as a grand theory, namely, the theory of the national soul based on the theory of Friedrich Carl Von Savigny. As a middle theory, it uses the legal theory of Talcott Parsons, famous for his structural functionalism theory, while the applied theory uses the theory of the law of happiness (utilitarianism) by Jeremy Bentham (applied theory). Referring to the analytical content in this journal, the results are specifically related to land registration and consolidation in border areas in the ecosystem perspective of the five-point zero disruption era, according to the mandate of constitutionalism which must be implemented by the Government in a sustainable manner (sustainability). The main aim is to strengthen the understanding of the sovereignty of the State and nation, understand the sovereignty of the people, understand Indonesia as a rule-of-law state, and at the same time strengthen the understanding of the national economy and social welfare.